Contested medicine cancer research and the military - Kutcher, Gerald (University of Chicago Press, 2009)
In the 1960s University of Cincinnati radiologist Eugene Saenger infamously conducted human experiments on patients with advanced cancer to examine how total body radiation could treat the disease. But, under contract with the Department of Defense, Saenger also used those same patients as proxies for soldiers to answer questions about combat effectiveness on a nuclear battlefield. Using the Saenger case as a means to reconsider cold war medical trials, Contested Medicine examines the inherent tensions at the heart of clinical studies of the time. Emphasizing the deeply intertwined and mutually.